Systematic review of patient and service outcome measures of remote digital technologies for cochlear implant and hearing aid users - Laird, Emma; Sucher, Cathy; Nakano, Kento; Ferguson, Melanie (Frontiers in Audiology and Otology, 2024)
The use of telehealth for cochlear implant (CI) and hearing aid service provision has the potential to provide efficient, effective, and equitable services to users. However, clinicians require evidence that remote technologies provide care that is equal, or superior to, standard delivery. There are many outcome measures used across audiology, however there is little consensus for a standardised approach to assessment. This systematic review aims to identify the outcome measures to assess remote technologies for CI and hearing aid users, as a first step in a larger project to develop a core outcome set for remote technologies in CI users. The inclusion of hearing aid studies was to ensure that all key outcome domains used within remote hearing rehabilitation were captured, as well as to compare differences in outcome domains between the two user groups. This systematic literature review of forty-nine articles revealed over 250 discrete outcomes. Outcome measures were grouped into core areas, outcome domains and outcome sub-domains. There were significant differences between studies of remote technologies for CI and hearing aid users. Studies assessing remote technology for CI users assessed significantly more outcomes in the ear and labyrinth domain (43% vs 10%) and studies assessing remote technology in hearing aid users assessed significantly more outcomes in the cognitive (28% vs 5%) and emotional (35% vs 10%) functioning domains. Outcome measures within the auditory functioning domain were also significantly different, with CI studies utilising more speech perception measures (95% vs 21%) and hearing aid studies utilising significantly more self-reported outcome measures (73% vs 19%). These results will inform the ongoing development of a core outcome set for remote technologies in CI users.